Preparation method and application of metal soft magnetic material

By covering the inorganic oxide insulating layer and ferrite phase layer on the surface of the metal soft magnetic powder, performing high-temperature annealing and spraying insulating paint, the problem of improving the permeability and magnetic loss of soft magnetic composite materials is solved, and low loss and high performance in high-frequency applications are achieved.

CN119833304APending Publication Date: 2025-04-15BATTFLEX (WUHAN) TECH CO LTD

Patent Information

Application Number
CN202510017994.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

While the prior art improves the magnetic permeability of soft magnetic composite materials and reduces magnetic loss, it is difficult to avoid the magnetic dilution effect, resulting in a decrease in saturation magnetization and magnetic permeability.

Method used

The metal soft magnetic powder surface is coated with an inorganic oxide insulating layer and ferrite phase layer through atomic layer deposition technology, combined with high temperature annealing treatment and spraying insulating paint, a metal soft magnetic composite material with high magnetic permeability and low magnetic loss is prepared.

Benefits of technology

In the field of high-frequency applications, the low loss and high performance of soft magnetic materials are achieved, the magnetic permeability is improved, and the magnetic loss is reduced, avoiding the magnetic dilution effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833304A_ABST
    Figure CN119833304A_ABST
Patent Text Reader

Abstract

According to the preparation method and application of the metal soft magnetic composite material, the surface of the metal soft magnetic powder is coated with the metal oxide insulating layer through the ALD technology, then the characteristics that the ferrite phase layer is high in resistivity, low in loss and good in high-frequency characteristic are utilized, insulating coating is conducted on the surface through the ALD technology, and the metal soft magnetic composite material is obtained. And a ferrite coating layer is formed on the surface of the metal soft magnetic powder during high-temperature annealing, so that electric contact among particles is blocked, the resistivity of the soft magnetic material is improved, and the eddy-current loss at high frequency is reduced, thereby improving the high-frequency performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic material preparation, and in particular to a preparation method and application of a metallic soft magnetic material. Background Art

[0002] Soft magnetic materials, as magnetic materials with high magnetic permeability, are used to confine and guide magnetic fields in electrical, electromechanical and magnetic devices, such as electromagnets, transformers, motors, inductors and magnetic material components. These components are usually made into different shapes and sizes by molding soft magnetic powder in a mold under high pressure. The key properties of soft magnetic materials are high resistivity, high saturation flux density and high magnetic permeability. Magnetic permeability is defined as the ratio of induced magnetic flux to magnetizing force or magnetic field strength. High magnetic permeability means that the material can guide the magnetic field more effectively and reduce the leakage of the magnetic field. When magnetic materials are exposed to rapidly changing magnetic fields, the total energy of the core will be reduced due to the occurrence of hysteresis loss and / or eddy current loss. Hysteresis loss is caused by the energy consumption necessary to overcome the magnetic force retained within the core component. High resistivity helps to reduce eddy current losses.

[0003] In the preparation of magnetic cores, the coating of soft magnetic materials is particularly important. It is necessary to coat the surface of the metal magnetic powder with a layer of high-resistance insulating medium to block the eddy currents between the powders. This plays a decisive role in improving the resistivity of the overall material of the magnetic powder core and reducing high-frequency losses.

[0004] At present, insulating materials can be mainly divided into organic insulating agents and inorganic insulating agents. Organic insulating agents mainly include resins with excellent insulation and softness, such as silicone resin, epoxy resin, phenolic resin, etc., but their heat resistance is extremely poor and they will decompose during high-temperature stress relief annealing treatment, thereby increasing magnetic loss and causing deterioration of magnetic properties. Inorganic insulating agents include inorganic materials with good high temperature resistance such as phosphates, silica and alumina. Chinese patent CN100409979C uses silica to coat carbonyl Fe powder, which greatly improves the resistivity of soft magnetic composite materials. Chinese patent CN104070161B uses silica / epoxy resin composites to coat Fe powder, combining the advantages of organic and inorganic coating materials, improving the resistivity of soft magnetic composite materials, and reducing eddy current losses.

[0005] Atomic layer deposition is an efficient thin film growth method that can form a uniform and conformal thin layer grown with sub-nanometer precision on the substrate surface. In recent years, atomic layer deposition has developed from the original planar surface deposition to complex surface deposition, especially for the surface coating of micro-nano particles, which can optimize the film thickness, density and uniformity while improving the physical and chemical properties of the particles. EU patent EP4087694A1 uses atomic layer deposition to coat multiple layers of different solid oxide layers on the surface of soft magnetic powder, including more than one layer of first solid oxide and at least one layer of second solid oxide, more than one layer of first solid oxide and at least one layer of second solid oxide are arranged alternately, and each of the solid oxides is one of Al, Si, Hf, Zn, Zr, Co, Mn, Ni and Ti. Chinese patent CN112466589B is similar to this patent. It uses CVD coating method to coat aluminum oxide, silicon oxide and titanium oxide on the surface of soft magnetic powder, and the magnetic loss is reduced to 601~635mW / cm 3 , the coercive force is reduced to 44~51A / m. In addition, Chinese patent CN115547606B uses atomic layer deposition to coat the surface of soft magnetic powder with polyimide. Without sacrificing the magnetic permeability performance, the loss of magnetic powder core material is significantly reduced to 145~153 mW / cm 3 , a metal magnetic powder core with high oxidation resistance temperature, high crushing strength, low magnetic loss and high magnetic permeability is obtained. However, the magnetic permeability of the magnetic powder core obtained by Chinese patents CN112466589B and CN115547606B at 50kHz / 100mT does not exceed 90.

[0006] However, whether it is organic materials or inorganic oxides, although the resistivity of soft magnetic composite materials has been improved to a certain extent, since they are all non-magnetic phases, their introduction will produce a magnetic dilution effect, reducing the saturation magnetization intensity and magnetic permeability, which is not conducive to obtaining a higher magnetic permeability.

[0007] Using magnetic ferrite materials instead of traditional non-magnetic phase materials as insulating coatings provides a possibility for people to study the formulation of soft magnetic composite materials. Chinese patent CN104550940B mixes metal magnetic powder with soft magnetic ferrite, and then forms a coating layer through microwave high-temperature heat treatment, thereby improving the magnetic permeability of the soft magnetic composite material. Chinese patent CN102136331B composites metal magnetic powder with nickel-zinc ferrite, densifies and sinters it using spark plasma sintering technology, thereby improving the soft magnetic properties of the soft magnetic composite material. However, the preparation cost of spark plasma sintering technology is high, and it is difficult to achieve mass production. Manganese-zinc ferrite and nickel-zinc ferrite are also used as insulating media to improve the magnetic permeability of soft magnetic composite materials. Therefore, how to achieve low loss and high performance of soft magnetic materials in high-frequency applications is an urgent problem to be solved. Summary of the invention

[0008] In order to solve the deficiencies in the prior art, the present invention provides a method for preparing a metal soft magnetic composite material, comprising the following steps: S1. The metal soft magnetic powder is insulated and coated by atomic layer deposition technology to obtain a metal soft magnetic powder coated with an insulating layer, wherein the insulating layer is an inorganic oxide; S2. The metal soft magnetic powder coated with the insulating layer obtained in step S1 is again insulated and coated by atomic layer deposition technology to obtain a composite metal soft magnetic powder coated with a ferrite phase layer; S3. The composite metal soft magnetic powder is subjected to high temperature annealing in a vacuum or inert gas to obtain an annealed composite metal soft magnetic powder; S4. Mix the annealed composite metal soft magnetic powder with a binder and a release agent, press the mixed powder into a shape, and then perform annealing heat treatment in a vacuum or inert gas, spray insulating paint, and obtain a metal soft magnetic composite material.

[0009] Furthermore, the soft magnetic powder is at least one of pure iron powder, iron-silicon alloy powder, iron-aluminum alloy powder, iron-silicon-aluminum alloy powder, iron-chromium alloy powder, iron-nickel alloy powder, and iron-nickel-molybdenum alloy powder.

[0010] Furthermore, in the step S1, the thickness of the insulating layer of the metal soft magnetic powder coated with the insulating layer is 0.5-5 nm.

[0011] Furthermore, the inorganic oxide of the insulating layer includes one of Al2O3, SiO2, TiO2, ZrO2, MgO, and HfO2.

[0012] Furthermore, the particle size of the soft magnetic powder ranges from 1 to 100 μm, and D50 is 10 μm.

[0013] Furthermore, in step S2, the thickness of the ferrite phase layer is 5-50 nm.

[0014] Furthermore, the ferrite phase layer includes a spinel structure and a garnet structure.

[0015] Furthermore, the step S2 includes: placing the metal soft magnetic powder coated with the insulating layer in a porous container, placing the porous container in a reaction chamber, or placing the metal soft magnetic powder coated with the insulating layer in the reaction chamber, using an inert gas to replace the gas in the reaction chamber, fluidizing the metal soft magnetic powder with the inert gas, or rotating the porous container to achieve the effect of dispersing the metal soft magnetic powder, using the inert gas to alternately load the first precursor and the oxygen source gas into the reaction chamber in a pulsed manner, and purging the residual gas with the inert gas during the alternation, the temperature of the reaction chamber is set to 160~300℃, the pressure is set to 40~150Pa, and repeating the cycle of step S2 until the ferrite phase layer reaches 5-50nm.

[0016] Furthermore, the spinel structured ferrite includes manganese zinc ferrite and nickel zinc ferrite, and the spinel structured ferrite phase layer is composed of M y Fe 3-y O4 represents, wherein 0<y≤1, M: a metal element serving as a divalent cation containing at least Mn and Zn or Ni and Zn; The first precursor includes a precursor of iron oxide, a precursor containing at least manganese oxide and zinc oxide, or a precursor containing at least nickel oxide and zinc oxide.

[0017] Furthermore, the garnet structured ferrite is composed of R 3 Fe 5 O 12 Indicates that R is a rare earth element; The first precursor includes a precursor of iron oxide and a precursor of R oxide.

[0018] Furthermore, the precursor of the oxide of R includes one or more of a precursor of CeO2, a precursor of Gd2O3, a precursor of Y2O3, a precursor of Yb2O3, and a precursor of Sm2O3.

[0019] Furthermore, in step S3, the temperature of the high temperature annealing treatment is 500-900° C., and the treatment time is 1 h-3 h.

[0020] Furthermore, the annealing temperature is preferably 750° C., and the annealing time is preferably 90 minutes.

[0021] Furthermore, in S4, the adhesive is one or more of phenolic resin, epoxy resin, silicone resin, polyvinyl fluoride, melamine resin, low melting point glass powder, SiO2, and the release agent is one or more of zinc stearate, barium stearate, calcium stearate or molybdenum disulfide. The mass proportion of the adhesive to the composite metal soft magnetic powder is 0.5~2.5%, and the mass proportion of the release agent to the composite metal soft magnetic powder is 0.5~2.0%.

[0022] A composite metal soft magnetic powder is obtained by using steps S1 to S3 of the method for preparing the metal soft magnetic composite material, and comprises particles coated with the ferrite phase layer, wherein the particles are the metal soft magnetic powder coated with the insulating layer.

[0023] The soft magnetic powder is at least one of pure iron powder, iron-silicon alloy powder, iron-aluminum alloy powder, iron-silicon-aluminum alloy powder, iron-chromium alloy powder, iron-nickel alloy powder, and iron-nickel-molybdenum alloy powder.

[0024] The thickness of the insulating layer is 0.5-5 nm, and the insulating layer is an inorganic oxide.

[0025] The particle size of the soft magnetic powder is in the range of 1 to 100 μm, and D50 is 10 μm.

[0026] The ferrite phase layer includes a spinel structure and a garnet structure.

[0027] The spinel structured ferrite includes manganese zinc ferrite and nickel zinc ferrite. The spinel structured ferrite phase layer is composed of Mn-Zn ferrite and Ni-Zn ferrite. y Fe 3-y O4 represents, wherein 0<y≤1, M: a metal element used as a divalent cation containing at least Mn and Zn or Ni and Zn; the garnet structured ferrite is composed of R 3 Fe 5 O 12 Indicates that R is a rare earth element.

[0028] The composite metal soft magnetic powder increases magnetic permeability and reduces magnetic loss by coating the ferrite phase layer, and prevents the ferrite phase layer from reacting with the metal soft magnetic powder at high temperature to reduce magnetic permeability and increase magnetic loss by coating the insulating layer; the thickness of the insulating layer and ferrite phase layer of the composite metal soft magnetic powder is nanometer level, which reduces the magnetic dilution effect on the metal soft magnetic powder.

[0029] The present invention also provides application of the metal soft magnetic composite material prepared by the preparation method of the metal soft magnetic composite material in preparing a metal magnetic powder core. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the ALD coated 1 nanometer aluminum oxide insulating layer and the 10 nanometer manganese-zinc ferrite metal soft magnetic material in Example 1; in the image, the iron-silicon-aluminum alloy powder is coated evenly and densely, and no obvious coating marks can be seen; Figure 2 The SEM images of the sheet-shaped sendust material at different stages of the method of the present invention are shown; (a) is before coating with ferrite, (b) is before annealing after coating with ferrite, and (c) is after coating with ferrite and annealing; Figure 2 It is shown that the coating method of the present invention can also achieve uniform and dense insulation coating for flaky soft magnetic materials. DETAILED DESCRIPTION

[0031] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0032] A method for preparing a metal soft magnetic composite material comprises the following steps: S1. Insulation coating is performed on metal soft magnetic powder by atomic layer deposition technology to obtain metal soft magnetic powder coated with an insulating layer; the soft magnetic powder is at least one of pure iron powder, iron-silicon alloy powder, iron-aluminum alloy powder, iron-silicon-aluminum alloy powder, iron-chromium alloy powder, iron-nickel alloy powder, and iron-nickel-molybdenum alloy powder; and the insulating layer is one of Al2O3, SiO2, TiO2, ZrO2, MgO, and HfO2.

[0033] The particle size of the soft magnetic powder is in the range of 1 to 100 μm, D50 is 10 μm, and the soft magnetic powder is spherical or flaky.

[0034] The atomic layer deposition technology specifically includes the following steps: placing metal soft magnetic powder in a reaction chamber, replacing the gas in the reaction chamber with an inert gas, using the inert gas as a carrier gas, and alternately passing the oxygen source gas and the precursor A into the reaction chamber in a pulsed form, and purging the residual gas with the inert gas during the alternation. The reaction pressure is 40 to 150 Pa, and the atomic layer deposition cycle is repeated for multiple times until the thickness of the insulating layer is 0.5 nm to 5 nm. The precursor A is a mixture of one or more of volatile silicon ions, metal alkylamino salts, metal organic compounds, halides, alkoxides, and metal β-diketone complexes. The metal ions in the metal alkylamino salts, metal organic compounds, halides, alkoxides, and metal β-diketone complexes are aluminum, magnesium, titanium, zirconium, and hafnium ions.

[0035] S2. The metal soft magnetic powder coated with the insulating layer obtained in step S1 is again insulated and coated by atomic layer deposition technology to obtain a composite metal soft magnetic powder coated with a ferrite phase layer; the thickness of the coating layer is 5nm-50nm.

[0036] The ferrite phase layer includes spinel structure and garnet structure.

[0037] The step S2 comprises: placing the metal soft magnetic powder coated with the insulating layer in a porous container, placing the porous container in a reaction chamber, or placing the metal soft magnetic powder coated with the insulating layer in the reaction chamber, replacing the gas in the reaction chamber with an inert gas, fluidizing the metal soft magnetic powder with the inert gas, or rotating the porous container to achieve the effect of dispersing the metal soft magnetic powder, alternately loading the first precursor and the oxygen source gas into the reaction chamber in a pulsed manner with the inert gas, purging the residual gas with the inert gas during the alternation, setting the temperature of the reaction chamber to 160-300°C, and the pressure to 40-150Pa, and repeating the step S2 until the ferrite phase layer reaches 5-50nm.

[0038] S3. The composite metal soft magnetic powder is placed in a high temperature furnace and subjected to high temperature annealing treatment in an inert gas atmosphere to obtain the annealed composite metal soft magnetic powder. The ferrite coated on the outside of the composite metal soft magnetic powder makes the coating layer denser under the action of high temperature annealing, further blocking the electrical contact between the powder particles, and effectively improving the resistivity of the magnetic powder core.

[0039] The spinel structure ferrites include manganese zinc ferrite and nickel zinc ferrite. y Fe 3-y O4 represents, wherein 0<y≤1, M: a metal element used as a divalent cation containing at least Mn and Zn or Ni and Zn. The first precursor includes a precursor of iron oxide in Table 1, a precursor containing at least manganese oxide and zinc oxide, or a precursor containing at least nickel oxide and zinc oxide.

[0040] Garnet structure ferrite is composed of R 3 Fe 5 O 12 It indicates that R is a rare earth element, R includes one of Ce, Gd, Y, Yb, and Sm, and the first precursor includes one or more of the iron oxide precursor in Table 2, the precursor containing at least CeO2, the precursor of Gd2O3, the precursor of Y2O3, the precursor of Yb2O3, and the precursor of Sm2O3.

[0041] The annealing temperature is preferably 750° C. and the annealing time is 90 minutes.

[0042] S4. Add 0.5-2.5% by weight of a binder to the annealed composite metal soft magnetic powder, and stir thoroughly under heating conditions until the mixture is dry and evenly mixed; finally, add 0.5-2.0% by weight of a release agent to the annealed composite metal soft magnetic powder and mix evenly to obtain magnetic powder to be formed; press the magnetic powder to be formed under a pressure of 600-2000MPa; use nitrogen or argon as a protective atmosphere, and place the formed magnetic powder in an environment of 400-650℃ for 30-120min; spray a layer of epoxy resin insulating paint on the surface of the heat-treated formed magnetic powder to obtain a finished product, that is, a metal soft magnetic composite material.

[0043] The weight of the metal magnetic powder is 10-20 g, and the anhydrous ethanol in the mixed solution is 100-150 mL. The binder is one or more of phenolic resin, epoxy resin, silicone resin, polyvinyl fluoride, melamine resin, low melting point glass powder, and SiO2. The release agent is one or more of zinc stearate, barium stearate, calcium stearate, or molybdenum disulfide.

[0044] Table 1 Table 2 Example 1 This embodiment provides a method for preparing a metal soft magnetic composite material, the preparation method comprising the following steps: S1. After the surface of the metal soft magnetic powder is coated with a 1nm thick Al2O3 insulating layer by atomic layer deposition technology, a soft magnetic powder coated with an insulating layer is obtained; the atomic layer deposition method includes the following steps: placing the metal soft magnetic powder in an ALD fluidized reaction chamber, evacuating and replacing nitrogen three times, heating the reaction chamber to 200°C, and maintaining the reaction chamber at a pressure of 100pa; using water vapor and trimethylaluminum as precursors, and nitrogen as the carrier gas of the precursor to alternately pass the precursor into the closed reaction chamber in pulse form, and high-purity nitrogen is purged between pulses. Residual gas. In this embodiment, the metal soft magnetic powder is selected from iron silicon aluminum alloy powder, and the iron silicon aluminum alloy powder contains Si 9%, Al 6%, and the rest is Fe by weight, D50 is 10μm, and the particle size range is 1~100μm.

[0045] S2. After coating the surface of the metal soft magnetic powder coated with the insulating layer with a 10 nm thick ferrite coating layer by atomic layer deposition technology, a composite metal soft magnetic powder is obtained; the atomic layer deposition method comprises the following steps: placing the metal soft magnetic powder coated with the insulating layer obtained in S1 in an ALD fluidized reaction chamber, evacuating and replacing nitrogen three times, heating the reaction chamber to 230°C, and maintaining the pressure of the reaction chamber at 150pa; Select precursor B, pulse into the reaction chamber under the N2 flow rate of 50sccm, adsorb on the metal soft magnetic powder coated with the insulating layer until 150Pa, and keep for 60 seconds, then purge with 50sccm N2 to take away the remaining precursor B, the N2 purge time is 30s, similarly, the oxygen source pulses into the reaction chamber under the N2 flow rate of 50sccm until the pressure reaches 150Pa and keep for 60 seconds, and reacts with the precursor B chemically adsorbed on the metal soft magnetic powder coated with the insulating layer to generate the corresponding metal oxide, the time is 60s, then the excess oxygen source and by-products are taken out of the reaction chamber by 50sccm N2 purge, the purge time is 30s, thus completing the ALD deposition cycle of the metal oxide; According to Table 2, the precursors C and D are selected, and pulsed into the reaction chamber under the N2 flow rate of 50sccm, adsorbed on the metal soft magnetic powder coated with the insulating layer until 150Pa, and maintained for 60 seconds, and then 50sccm N2 is used to purge and take away the remaining precursors C and D, and the N2 purge time is 30s. Similarly, the oxygen source is pulsed into the reaction chamber under the N2 flow rate of 50sccm until the gas pressure reaches 150Pa and maintained for 60 seconds, and reacts with the precursors C and D that have been chemically adsorbed on the metal soft magnetic powder coated with the insulating layer to generate the corresponding metal oxides, and the time is 60s. Subsequently, the excess oxygen source and by-products are taken out of the reaction chamber by 50sccm N2 purge, and the purge time is 30s, thus completing the ALD deposition cycle of the metal oxide; Repeat the above cycle several times, and then coat the surface of the metal soft magnetic powder coated with the insulating layer with a 10nm ferrite coating layer containing iron oxide, manganese oxide and zinc oxide. The molar proportion of zinc oxide in the ferrite coating layer is 20%, the molar proportion of manganese oxide is 30%, and the molar proportion of ferrite is 50%. 0.3 Zn 0.2 Fe 0.5 O 1.06 The ferrite layer is composed of

[0046] S3. The composite soft magnetic powder was subjected to high temperature annealing treatment in a nitrogen atmosphere at a temperature of 750°C for 2 h. After annealing, the following Figure 1 The composite metal soft magnetic powder after annealing is shown.

[0047] S4. Add 2.5% by weight of a binder to the annealed composite metal soft magnetic powder, and stir thoroughly under heating conditions until the mixture is dry and evenly mixed, wherein the binder is silicone resin; add 2.0% by weight of a release agent to the annealed composite metal soft magnetic powder and mix evenly, wherein the release agent is a mixture of zinc stearate and molybdenum disulfide in a mass ratio of 1:1 to obtain magnetic powder to be formed; press the magnetic powder to be formed under a pressure of 1500MPa into a ring-shaped formed magnetic powder with an outer diameter of 23.6mm, an inner diameter of 14.4mm, and a height of 8.89mm; use argon as a protective atmosphere, place the formed magnetic powder in an environment of 650℃ for 30 minutes to prepare a heat-treated formed magnetic powder; spray a layer of epoxy resin insulating paint on the surface of the heat-treated formed magnetic powder to obtain a finished product, that is, an iron-silicon-based soft magnetic composite material.

[0048] The inductor coil with 20 turns was wound with enameled wire with a diameter of 0.8 mm and a length of 0.9 m on the iron-silicon-aluminum based soft magnetic composite material. The magnetic properties of the soft magnetic composite material were measured as follows: (1) Magnetic permeability of soft magnetic composite material: 189; (2) The density of the soft magnetic composite material is 7.76 g / cm3 ; (3) After annealing at 650℃, the coercivity is 142.3A / m; (4) Under 100kHz / 1V conditions, the quality factor Q=68; (5) At 50kHz / 100mT, the core loss is 178.3mW / cm 3 .

[0049] The magnetic permeability of the metal soft magnetic composite material obtained in Example 1 is better than that of the magnetic powder cores obtained in CN112466589B and CN115547606B, and the magnetic powder core loss of the metal soft magnetic composite material obtained in Example 1 is lower.

[0050] Example 2 The method of Example 1 is adopted to prepare a metal soft magnetic composite material. The difference from Example 1 is that the insulating layer is 3nm thick zirconium oxide, the main components of ferrite include ZnO 20mol%, MnO 30mol%, and the balance is Fe2O3 in molar percentage. After coating, it is annealed at 750°C in a nitrogen atmosphere for 90 minutes.

[0051] Example 3 The method of Example 1 is adopted to prepare a metal soft magnetic composite material. The difference from Example 1 is that the insulating layer is 3nm thick titanium oxide, the main components of ferrite include ZnO 20mol%, NiO 30mol%, and the balance is Fe2O3 in molar percentage, and after coating, it is annealed at 750°C in a nitrogen atmosphere for 90 minutes.

[0052] Example 4 The method of Example 1 was adopted to prepare a metal soft magnetic composite material, which was different from Example 1 in that there was no insulating layer coating, and the main components of ferrite included ZnO 20mol%, NiO 30mol%, and the balance was Fe2O3 in molar percentage. After coating, it was annealed at 750°C in a nitrogen atmosphere for 90 minutes.

[0053] On the Sendust soft magnetic composite material, an enameled wire with a wire diameter of 0.8 mm and a wire length of 0.9 m was used to wind 20 turns of inductor coil. Since the Sendust alloy powder of this embodiment is not coated with an insulating layer, after high-temperature annealing, the ferrite and alloy on the surface of the Sendust alloy powder react, and the magnetic properties of the soft magnetic composite material are measured as follows: (1) Magnetic permeability of soft magnetic composite material: 145; (2) The density of the soft magnetic composite material is 7.76 g / cm 3 ; (3) After annealing at 650℃, the coercivity is 168.3A / m; (4) Under 100kHz / 1V conditions, the quality factor Q=46; (5) At 50kHz / 100mT, the core loss is 386.9mW / cm 3 .

[0054] The magnetic permeability of the metal soft magnetic composite material obtained in Example 4 is better than that of the magnetic powder cores obtained in CN112466589B and CN115547606B, but the magnetic powder core loss of the metal soft magnetic composite material obtained in Example 4 is higher.

[0055] Example 5 The method of Example 1 was adopted to prepare the metal soft magnetic composite material. The difference from Example 1 was that the annealing temperature was 300° C., and the spinel ferrite structure could not be formed.

[0056] Example 6 The method of Example 1 is used to prepare a metal soft magnetic composite material. The difference from Example 1 is that the ferrite main component includes 37.5 mol% of Gd2O3 or Y2O3 or Yb2O3 or Sm2O3 in molar percentage, and the balance is Fe2O3. After coating, it is annealed at 750°C in a nitrogen atmosphere for 90 minutes.

[0057] The atomic layer deposition method in step S2 includes the following steps: placing the metal soft magnetic powder coated with the insulating layer obtained in S1 in an ALD fluidized reaction chamber, evacuating and replacing nitrogen three times, heating the reaction chamber to 230° C., and maintaining the pressure of the reaction chamber at 150 Pa; Select precursor B, pulse into the reaction chamber under the N2 flow rate of 50sccm, adsorb on the metal soft magnetic powder coated with the insulating layer until 150Pa, and keep for 60 seconds, then purge with 50sccm N2 to take away the remaining precursor B, the N2 purge time is 30s, similarly, the oxygen source pulses into the reaction chamber under the N2 flow rate of 50sccm until the pressure reaches 150Pa and keep for 60 seconds, and reacts with the precursor B chemically adsorbed on the metal soft magnetic powder coated with the insulating layer to generate the corresponding metal oxide, the time is 60s, then the excess oxygen source and by-products are taken out of the reaction chamber by 50sccm N2 purge, the purge time is 30s, thus completing the ALD deposition cycle of the metal oxide; According to Table 2, a precursor is selected as one of I~L, and the reaction chamber is heated according to the corresponding precursor according to Table 2. It is pulsed into the reaction chamber under the N2 flow rate of 50sccm, adsorbed on the metal soft magnetic powder coated with the insulating layer until 150Pa, and maintained for 60 seconds, and then 50sccm N2 is used to purge and take away the remaining precursor I~L. The N2 purge time is 30s. Similarly, an oxygen source is pulsed into the reaction chamber under the N2 flow rate of 50sccm until the gas pressure reaches 150Pa and maintained for 60 seconds, and reacts with one of the precursors I~L that has been chemically adsorbed on the metal soft magnetic powder coated with the insulating layer to generate a corresponding metal oxide for 60s. Subsequently, excess oxygen source and by-products are taken out of the reaction chamber by 50sccm N2 purge, and the purge time is 30s, thus completing the ALD deposition cycle of the metal oxide; Repeat the above cycle several times, and then coat the surface of the metal soft magnetic powder coated with the insulating layer with a 10nm ferrite coating layer containing iron oxide, Gd2O3 or Y2O3 or Yb2O3 or Sm2O3, in which the molar amount of Gd2O3 or Y2O3 or Yb2O3 or Sm2O3 in the ferrite coating layer accounts for 37.5%, and the molar amount of ferrite accounts for 62.5%. 0.375 Fe 0.625 O 1.5 The ferrite layer is composed of R. R includes one of Gd, Y, Yb, and Sm.

[0058] Comparative Example 1 This comparative example provides a method for preparing a metal soft magnetic composite material, wherein steps S3 to S4 are the same as those in Example 1, except that step S1 is not used to coat the surface of the metal soft magnetic powder with an Al2O3 insulating layer, and in step S2, the atomic layer deposition technology is replaced with a chemical plating process to coat the ferrite phase layer with a spinel structure.

[0059] For example: Step S2 of this comparative example is to immerse the sendust aluminum alloy powder in ion exchange water, the ion exchange water has a metal chloride MCl2 (wherein M represents Fe, Ni, Zn, Cu, Mn or Mg in the ion exchange water), and in this embodiment, M is Fe, Zn, and Mn, and slowly pour the aqueous solution of metal chloride onto the sendust aluminum alloy powder, and adjust the pH value to 7.0 by using an aqueous NaOH solution. The mixed solution is kept at a constant temperature of 70°C, and air is blown in while slowly stirring for 0.3-3 hours, thereby forming a ferrite coating powder on the surface of the sendust aluminum alloy powder. Then, the ferrite coating powder is filtered, washed in water and dried to obtain a composite metal soft magnetic powder.

[0060] The magnetic permeability of the metal soft magnetic composite material obtained by step S4 in this comparative example is measured to be 75, and the magnetic powder core loss is 358.8 mW / cm at 50 kHz / 100 mT.3 .

[0061] Comparative Example 2 This comparative example provides a method for preparing a soft magnetic composite material. Step S1 and steps S3-S4 are the same as those in Example 1, except that in step S2, the atomic layer deposition technology is replaced by a chemical plating process to coat the ferrite phase layer of the spinel structure.

[0062] For example: Step S2 of this comparative example is to immerse the metal soft magnetic powder coated with the insulating layer in ion exchange water, the ion exchange water has a metal chloride MCl2 (where M represents Fe, Ni, Zn, Cu, Mn or Mg in the ion exchange water), and in this embodiment, M is Fe, Zn, and Mn. The aqueous solution of the metal chloride is slowly poured onto the metal soft magnetic powder coated with the insulating layer, and the pH value is adjusted to 7.0 by an aqueous NaOH solution. The mixed solution is kept at a constant temperature of 70°C, and air is blown in while slowly stirring for 0.3-3 hours, thereby forming a ferrite coating powder on the surface of the metal soft magnetic powder coated with the insulating layer. Then, the ferrite coating powder is filtered, washed in water and dried to obtain a composite soft magnetic powder.

[0063] The magnetic permeability of the metal soft magnetic composite material obtained by the step S4 in this comparative example is measured to be 103, and the magnetic powder core loss is 844.7 mW / cm at 50kHz / 100mT. 3 .

[0064] The performance of the sendust aluminum alloy powder, the sendust aluminum powder coated with only the insulating layer, Example 1, Example 4, and the soft magnetic material before the step S3 treatment of Example 1 was tested. The results are shown in Table 3. Compared with Example 4, Example 1 is coated with an additional layer of ferrite, which improves the insulation capacity. The soft magnetic material before the step S3 treatment of Example 1 has a strong insulation capacity, but the step S4 treatment is unavoidable in the preparation of the magnetic core material. The high-pressure pressing increases the temperature of the magnetic core, so that the soft magnetic material undergoes a high-temperature annealing treatment, which reduces the resistivity.

[0065] Table 3

Claims

1. A method for preparing a metal soft magnetic composite material, characterized in that: The following steps are involved: S1. The metal soft magnetic powder is insulated and coated by atomic layer deposition technology to obtain a metal soft magnetic powder coated with an insulating layer, wherein the insulating layer is an inorganic oxide; S2. The metal soft magnetic powder coated with the insulating layer obtained in step S1 is again insulated and coated by atomic layer deposition technology to obtain a composite metal soft magnetic powder coated with a ferrite phase layer; S3. The composite metal soft magnetic powder is subjected to high temperature annealing in a vacuum or inert gas to obtain an annealed composite metal soft magnetic powder; S4. Mix the annealed composite metal soft magnetic powder with a binder and a release agent, press the mixed powder into a shape, and then perform annealing heat treatment in a vacuum or inert gas, spray insulating paint, and obtain a metal soft magnetic composite material.

2. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: The soft magnetic powder is at least one of pure iron powder, iron-silicon alloy powder, iron-aluminum alloy powder, iron-silicon-aluminum alloy powder, iron-chromium alloy powder, iron-nickel alloy powder, and iron-nickel-molybdenum alloy powder.

3. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: In the step S1, the thickness of the insulating layer of the metal soft magnetic powder coated with the insulating layer is 0.5-5 nm.

4. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: The inorganic oxide of the insulating layer includes one of Al2O3, SiO2, TiO2, ZrO2, MgO, and HfO2.

5. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: The particle size of the soft magnetic powder is in the range of 1 to 100 μm, and D50 is 10 μm.

6. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: The thickness of the ferrite phase layer in step S2 is 5-50 nm.

7. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: The ferrite phase layer includes a spinel structure and a garnet structure.

8. The method for preparing the metal soft magnetic composite material according to claim 7, characterized in that: The step S2 comprises: placing the metal soft magnetic powder coated with the insulating layer in a porous container, placing the porous container in a reaction chamber, or placing the metal soft magnetic powder coated with the insulating layer in the reaction chamber, replacing the gas in the reaction chamber with an inert gas, fluidizing the metal soft magnetic powder with the inert gas, or rotating the porous container to achieve the effect of dispersing the metal soft magnetic powder, alternately loading the first precursor and the oxygen source gas into the reaction chamber in a pulsed manner with the inert gas, purging the residual gas with the inert gas during the alternation, setting the temperature of the reaction chamber to 160-300°C, and the pressure to 40-150Pa, and repeating the step S2 until the ferrite phase layer reaches 5-50nm.

9. The method for preparing the metal soft magnetic composite material according to claim 8, characterized in that: The spinel structured ferrite includes manganese zinc ferrite and nickel zinc ferrite. The spinel structured ferrite phase layer is composed of Mn-Zn ferrite and Ni-Zn ferrite. y Fe 3-y O4 represents, wherein 0<y≤1, M: a metal element serving as a divalent cation containing at least Mn and Zn or Ni and Zn; The first precursor includes a precursor of iron oxide, a precursor containing at least manganese oxide and zinc oxide, or a precursor containing at least nickel oxide and zinc oxide.

10. The method for preparing the metal soft magnetic composite material according to claim 8, characterized in that: The garnet structure ferrite is composed of R 3 Fe 5 O 12 Indicates that R is a rare earth element; The first precursor includes a precursor of iron oxide and a precursor of R oxide.

11. The method for preparing the metal soft magnetic composite material according to claim 8, characterized in that: The precursor of the oxide of R includes one or more of a precursor of CeO2, a precursor of Gd2O3, a precursor of Y2O3, a precursor of Yb2O3, and a precursor of Sm2O3.

12. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: In step S3, the high temperature annealing treatment is performed at a temperature of 500-900° C. and a treatment time of 1 h-3 h.

13. The method for preparing the metal soft magnetic composite material according to claim 1, characterized in that: In S4, the adhesive is one or more of phenolic resin, epoxy resin, silicone resin, polyvinyl fluoride, melamine resin, low melting point glass powder, SiO2, and the release agent is one or more of zinc stearate, barium stearate, calcium stearate or molybdenum disulfide. The mass proportion of the adhesive to the composite metal soft magnetic powder is 0.5~2.5%, and the mass proportion of the release agent to the composite metal soft magnetic powder is 0.5~2.0%.

14. A composite metal soft magnetic powder, characterized in that: The method is obtained by using steps S1 to S3 of the preparation method according to any one of claims 1 to 13, comprising particles coated with the ferrite phase layer, wherein the particles are the metal soft magnetic powder coated with the insulating layer.

15. Use of the metal soft magnetic composite material prepared by the preparation method according to any one of claims 1 to 13 in preparing metal magnetic powder cores.

Citation Information

Patent Citations

  • Production of nano-SiO2 for coating carbonyl iron powder

    CN100409979C

  • High-efficiency soft magnetic composite material and preparation method thereof

    CN102136331B

  • A method for preparing an inorganic-organic composite binder-coated soft magnetic composite material

    CN104070161B

  • Method for coating metal magnetic powder with soft magnetic ferrite and method for preparing soft magnetic composite material therefrom

    CN104550940B

  • A CVD-coated iron-silicon alloy powder and an iron-silicon magnetic powder core and their preparation method

    CN112466589B

Cited By

  • Magnetic powder core with in-situ generated insulating coating layer as well as preparation method and application of magnetic powder core

    CN120878388A

  • A magnetic powder core with an in-situ generated insulation coating layer, a preparation method and application thereof

    CN120878388B

  • Preparation method of high-resistance spherical soft magnetic metal powder and composite material of high-resistance spherical soft magnetic metal powder

    CN121289490A